A review of Scatellini (Diptera: Ephydridae) from Brazil - Wayne N. Mathis; Luciane Marinoni; Daniel N.R. Costa (Zoologia (Curitiba), 2014)
Scatellini was proposed by Wirth & Stone, 1956 and currently includes 242 described species in nine genera. The tribe has representatives in all biogeographic regions and about 70 species occur in the Neotropical Region. Prior to this study, only two species were recorded from Brazil: Scatella obscura and Limnellia itatiaia. In this paper, species of Scatellini from Brazil are reviewed with an emphasis on the fauna from southern Brazil, where six new species have been discovered and are described herein: Scatella praia, S. plaumanni, S. rara, Scatophila darrowae, S. dianneae, and S. prainha. To facilitate identification of the tribe and included genera and species, we have included diagnoses of these taxa and have also provided an annotated key to the Neotropical genera in Scatellini. We have also provided illustrations of structures of the male terminalia of all included species of the genus Scatophila.